2014
DOI: 10.3389/fpsyg.2014.00225
|View full text |Cite
|
Sign up to set email alerts
|

Visual target distance, but not visual cursor path length produces shifts in motor behavior

Abstract: When using tools effects in body space and distant space often do not correspond. Findings so far demonstrated that in this case visual feedback has more impact on action control than proprioceptive feedback. The present study varies the dimensional overlap between visual and proprioceptive action effects and investigates its impact on aftereffects in motor responses. In two experiments participants perform linear hand movements on a covered digitizer tablet to produce ∩-shaped cursor trajectories on the displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…It was found that the previous forward model was still in effect in the first trial after a gain change, and was fully adjusted to the current gain within five strokes. For the n replication task, Wendker et al (2014) demonstrated reduced after-effects in gain repetition-trials compared to gain changetrials. This benefit from gain repetitions expresses the adjustment of the forward model (Wolpert & Flanagan, 2001).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…It was found that the previous forward model was still in effect in the first trial after a gain change, and was fully adjusted to the current gain within five strokes. For the n replication task, Wendker et al (2014) demonstrated reduced after-effects in gain repetition-trials compared to gain changetrials. This benefit from gain repetitions expresses the adjustment of the forward model (Wolpert & Flanagan, 2001).…”
Section: Introductionmentioning
confidence: 90%
“…So far, most studies demonstrated those transient bindings in discrete motor actions that required an immediate response to stimuli. These studies found after-effects in terms of short-term biases (e.g., in a Simon task: Stürmer, Leuthold, Soetens, Schröter, & Sommer, 2002;; in motor replication tasks: Ladwig, Sutter, & Müsseler, 2012Perrotin & d'Alessandro, 2016;Sack & Sutter, 2017;Wendker, Sack, & Sutter, 2014). For instance, Ladwig et al (2012.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wendker et al (2014) studied this phenomenon in a condition in which there where two sources of visual information available. First, participants were presented with two dots on a screen indicating movement starting point and movement target (visual target distance).…”
mentioning
confidence: 99%
“…The contributions to the present research topic range from how information from different senses and action control are linked and modulated by object affordances (Garrido-Vásquez and Schubö, 2014), by task-irrelevant information (Juravle et al, 2013;Wendker et al, 2014; for a review see Wesslein et al, 2014), by temporal and spatial coupling within and between senses (Cameron et al, 2014;Mueller and Fiehler, 2014;Rieger et al, 2014;Sugano et al, 2014) to childhood development of multisensory mechanisms (Jovanovic and Drewing, 2014).…”
mentioning
confidence: 99%